1997
DOI: 10.1021/ma961014l
|View full text |Cite
|
Sign up to set email alerts
|

Testosterone Receptor Binding Mimic Constructed Using Molecular Imprinting

Abstract: The molecular imprinting technique was used in the synthesis of polymers having a high affinity for testosterone. These polymers thus function as receptor binding mimics for the drug. Various polymerization conditions were examined in order to determine their influence on the binding strength and selectivity of the binding mimics. Using a series of similar steroids, we were able to identify features of the molecules which affect their affinity for the polymer matrix. The efficacy of covalent and noncovalent im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
63
0
1

Year Published

1998
1998
2008
2008

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 144 publications
(65 citation statements)
references
References 33 publications
1
63
0
1
Order By: Relevance
“…The capacity factor (k') was calculated as (t À t o ) / t o , where t is retention time of the solute and t o is the retention time of the void marker; the separation factor of a given nontemplate analyte was defined as a = k' t / k' x , where k' t and k' x is the capacity factors of the template and the other compound, respectively [10]. The imprinting factor (I) is defined as I = k' i / k' n where k' i and k n , refer to the imprinted and nonimprinted polymers [8].…”
Section: Chromatographic Evaluationmentioning
confidence: 99%
See 2 more Smart Citations
“…The capacity factor (k') was calculated as (t À t o ) / t o , where t is retention time of the solute and t o is the retention time of the void marker; the separation factor of a given nontemplate analyte was defined as a = k' t / k' x , where k' t and k' x is the capacity factors of the template and the other compound, respectively [10]. The imprinting factor (I) is defined as I = k' i / k' n where k' i and k n , refer to the imprinted and nonimprinted polymers [8].…”
Section: Chromatographic Evaluationmentioning
confidence: 99%
“…The amount of the bound template was determined as the difference between the amount in reference tubes (containing no polymer) and the amount of free Tst in the sample. The polymers imprinted against Tst, Aen and Adien as well as the nonimprinted one were synthesized under the conditions employed in our previous works [8,9]: template±monomer ratio 1 : 8, CHCl 3 as porogen. The structure of the templates used is very similar: Aen possesses a keto group at the C-17 position instead of the OH group in Tst, Adien contains an additional double bond between C-1 and C-2 compared with Aen (Fig.…”
Section: Batch Rebinding Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…In aprotic solvents such as acetonitrile and chloroform, ethyl adenine-9-acetate and N-Z-L-Glu MIPs were prepared successively with MAA as functional monomer [1,30]. Often, a large excess of MAA in the synthesis step is required for recognition to be observed and then only in solvents of low to medium polarity and hydrogen bond capacity [31]. The excess of functional monomer results in a portion not being associated with imprinted sites.…”
Section: Selection Of Functional Monomermentioning
confidence: 99%
“…For instance, Cheong et al have shown a higher absorption of estradiol by MIP imprinted for testosterone. 12 The time-dependent release of T from the MIP to water in the absence of Hy is summarized in Table II. It is apparent that even after 24 h, nearly 55% of the compound is retained in the MIP.…”
Section: Release Of T To Water In the Presence Of Hymentioning
confidence: 99%